Complexity of domestic violence in a South Asian context in Hong Kong: cultural and structural impact. Issue 1 (2nd January 2016) - Tonsing, Jenny C.
Abstract: With the dearth of empirical research related to the experiences of domestic violence among South Asian communities in Hong Kong, this study engages with migrant South Asian women's subjective understanding and experience of domestic violence. Presenting women's narratives of their experiences with domestic violence allow for a better understanding of the complexities that inform and shape women's experiences and decision-making in the face of partner violence. This empirical study investigated South Asian women's experience of domestic violence in the context of Hong Kong through in-depth interviews with 14 South Asian women who had experienced abuse and 6 helping professionals from 4 social service agencies. Analysis of the data revealed that the nature and context of abuse posed as a barrier in their help seeking. The findings highlight the importance of understanding the influence of cultural and structural conditions and the difficulties and complexities women face that increases women's vulnerability to abuse. This paper offers an analysis of how structures thereby come to impact on women's distress and vulnerability. The study also highlights the need for inclusive service provision for minority ethnic women experiencing domestic violence.